É correto afirmar que as raizes da função f(x) = x² + 2x -3 é (A) (1 , 3) (B) (-1, -3) (C) (-3 , 1) (D) (-1, 3)
Soluções para a tarefa
Respondido por
1
f(x) = x² + 2x -3
x² + 2x -3 = 0
Δ= 2² - 4 . 1 . (-3)
Δ= 4 + 12
Δ= 16
X= - 2 ±√16 / 2 .1
X= - 2 ± 4 / 2
X'= - 2 + 4 / 2 = 2 / 2 = 1
X"= - 2 - 4 / 2 = - 6 / 2 = - 3
S={ - 3 e 1 }
Alternativa (C) ( -3 , 1 )
x² + 2x -3 = 0
Δ= 2² - 4 . 1 . (-3)
Δ= 4 + 12
Δ= 16
X= - 2 ±√16 / 2 .1
X= - 2 ± 4 / 2
X'= - 2 + 4 / 2 = 2 / 2 = 1
X"= - 2 - 4 / 2 = - 6 / 2 = - 3
S={ - 3 e 1 }
Alternativa (C) ( -3 , 1 )
C4valeiro:
Obgd Amigo!
Perguntas interessantes